Dissertation Abstracts (Academy of Management Journal, 1963)
The article presents abstracts pertaining to management science. They include “A General Systems Approach to the Analysis of Managerial Functions,” by R. William Millman, “An Analysis of Management Functions as Influenced by Organized Labor: The Early Traditional Approach,” by Richard J. Whiting, and “The Impact of Scientific Management and Automation on the American Labor Force,” by Mohamed Salah El-Din El-Shanawani.